Software for physical education of preschool children in European countries - Moskalenko , N.; Matsola , K. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction and purpose of the study. The article presents a generalization of scientific literature and documentary materials regarding the provision of the educational process in preschool education institutions with educational programs. The purpose of the study is to analyze the content of curriculum for preschool education institutions in European countries in order to substantiate the possibilities of using their experience at the current stage of reforming the education system in Ukraine. Material and methods. Research was conducted at the Prydniprovsk State Academy of Physical Culture and Sport. The following methods were used during the research: theoretical analysis and generalization of data from scientific and methodological literature and documentary materials, comparison method, system analysis method. Results. In Europe, unlike Ukraine, there is a difference in the interpretation of the term “preschool education” and there are also different approaches to ensuring children’s access to early education and care. In many countries, the education of a child up to 3 years old is optional and is not covered by curriculum. Instead, it is regulated by law that it is mandatory for a child to get an education from the age of 4-5, before primary education. This stage of education is usually provided by state curriculum. We have identified many common features in the components of curriculums for preschool education institutions in European countries. It should be noted that considerable attention is paid to physical education as one of the important components of a child’s harmonious development. As a rule, the content of physical education includes learning basic motor actions, games, mastering the elements of some sports. Conclusions. European countries are trying to create a single educational space, including in the field of preschool education. The early education systems of European countries have many common features and are characterized by a comprehensive approach to children’s development. The structure of curriculum for preschool education institutions includes the following components: the study of languages, mathematics, science and technology, art, the surrounding world, and physical education. Special attention is paid to ensuring the physical development of children, their motor activity, integration into various types of activities.